2013
DOI: 10.1021/nn402348r
|View full text |Cite
|
Sign up to set email alerts
|

Electric Stress-Induced Threshold Voltage Instability of Multilayer MoS2 Field Effect Transistors

Abstract: We investigated the gate bias stress effects of multilayered MoS2 field effect transistors (FETs) with a back-gated configuration. The electrical stability of the MoS2 FETs can be significantly influenced by the electrical stress type, relative sweep rate, and stress time in an ambient environment. Specifically, when a positive gate bias stress was applied to the MoS2 FET, the current of the device decreased and its threshold shifted in the positive gate bias direction. In contrast, with a negative gate bias s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
193
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(210 citation statements)
references
References 45 publications
16
193
0
1
Order By: Relevance
“…3 and Table 1) considered in previous studies. [16][17][18][19]22,23,25 Adsorbate mediated hysteresis mechanism 18,19 is shown in Fig. 3a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and Table 1) considered in previous studies. [16][17][18][19]22,23,25 Adsorbate mediated hysteresis mechanism 18,19 is shown in Fig. 3a.…”
Section: Resultsmentioning
confidence: 99%
“…15 Comparison of previous reports on hysteresis in MoS 2 devices with this work is listed in Table 1. Hysteresis observed in previous studies [16][17][18] has been attributed to several possibilities such as adsorption of water molecules, [18][19][20][21] oxide traps close to MoS 2 , 22 oxide-MoS 2 interface traps 23,24 and gate voltage stress effects. 25 A lack of uniformity in the hysteresis data and consensus on its origin among the reports listed in Table 1 results, at least partly, from differences in measurement conditions as well as device architecture.…”
Section: Introductionmentioning
confidence: 91%
“…However, it has been shown that on the same substrate type variations in film morphology and film-substrate bonding strength can have major impacts on the material properties. 2,4 Furthermore, the film-substrate interaction have been shown to be non-stationary under thermal 2, 4 and electrical stresses, [6][7][8] and may differ significantly for the same substrate material but prepared differently (e.g., epitaxially grown vs. transferred). 4 Changes in surface morphology and film-substrate bonding during thermal annealing have been attributed to the unusual temperature evolution in the optical properties, 2, 4 whereas alternations in the interfacial states and surface contaminants under electrical stress have been suggested to be responsible for the instability of electrical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…4 Changes in surface morphology and film-substrate bonding during thermal annealing have been attributed to the unusual temperature evolution in the optical properties, 2, 4 whereas alternations in the interfacial states and surface contaminants under electrical stress have been suggested to be responsible for the instability of electrical characteristics. [6][7][8] Therefore, the answer to a question like how the substrate will impact the carrier saturation velocity of a 2D material is unlikely to be unique. [9][10][11] Furthermore, it is unclear how thermal annealing or unintended thermal stress during temperature dependent measurements will affect the material properties, and how will be the interplays of above mentioned "intrinsic" (substrate) and extrinsic perturbations responding to the annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Before light illumination, the depleted surface of the thin MoS 2 would be electrically positive attracting some dipole moment-containing molecules (adsorption). [31][32][33] During the light introduction to the region, some of photogenerated electrons release those surface molecules (desorption) and are trapped at the surface while others move to V in terminal. (Photo-generated holes are drained to the ground).…”
mentioning
confidence: 99%